16S rRNA gene sequencing analysis of gut microbiome in a mini‐pig diabetes model. Issue 1 (25th February 2022) - Niu, Miaomiao; Zhao, Yuqiong; Xiang, Lei; Jia, Yunxiao; Yuan, Jifang; Dai, Xin; Chen, Hua
Abstract: Background: Currently, increasing attention is being paid to the important role of intestinal microbiome in diabetes. However, few studies have evaluated the characteristics of gut microbiome in diabetic miniature pigs, despite it being a good model animal for assessing diabetes. Methods: In this study, a mini‐pig diabetes model (DM) was established by 9‐month high‐fat diet (HFD) combined with low‐dose streptozotocin, while the animals fed standard chow diet constituted the control group. 16S ribosomal RNA (rRNA) gene sequencing was performed to assess the characteristics of the intestinal microbiome in diabetic mini‐pigs. Results: The results showed that microbial structure in diabetic mini‐pigs was altered, reflected by increases in levels of Coprococcus_3 and Clostridium_sensu_stricto_1, which were positively correlated with diabetes, and decreases in levels of the bacteria Rikenellaceae, Clostridiales_vadinBB60_group, and Bacteroidales_RF16_group, which were inversely correlated with blood glucose and insulin resistance. Moreover, PICRUSt‐predicted pathways related to the glycolysis and Entner‐Doudoroff superpathway, enterobactin biosynthesis, and the l ‐tryptophan biosynthesis were significantly elevated in the DM group. Conclusion: These results reveal the composition and predictive functions of the intestinal microbiome in the mini‐pig diabetes model, further verifying the relationship between HFD, gut microbiome, and diabetes, and providing novel insights into the application of the mini‐pig diabetes model in gut microbiome research. Abstract : Microbial structure in diabetic mini‐pigs was altered, reflected by increasing in Lactobacillus, Peptococcus, Coprococcus_3, Clostridium_sensu_stricto_1, and Paludibacter, and decreasing in the bacteria Rikenellaceae_RC9_gut_group, Prevotella_7, and some unclassified genera of p_2534_18B5_gut_group, Clostridiales_vadinBB60_group, Bacteroidales_RF16_group, Izimaplasmatales, and Peptococcaceae .